Study of bronchoalveolar lavage fluid in paracoccidioidomycosis: cytopathology and alveolar macrophage function in response to gamma interferon; comparison with blood monocytes - Calvi, S. A.; Soares, AMVC; Peracoli, MTS; Franco, M.; Ruiz, R. L.; Marcondes-Machado, J.; Fecchio, D.; Mattos, MCI; Mendes, R. P. (Elsevier B.V., 2003)
Patients with paracoccidioidomycosis (PCM) present marked involvement of the lungs during the course of the mycosis. The purpose of this work was to obtain bronchoalveolar lavage (BAL) fluid from these patients to study the cytopathology, TNF levels and the oxidative and fungicidal response of alveolar macrophages (AMs) to in vitro incubation with recombinant IFN-gamma. To compare the lung and blood compartments, these determinations were also made in plasma and blood monocytes (BMs) obtained from the same patients. The cytopathology of BAL fluid revealed a predominance of macrophages, but with the presence of neurrophil exudation, and rare lymphocytes and epithelioid and giant cells. Comparison of the oxidative status and fungicidal activity of AMs and circulating BMs demonstrated that both cell types are highly activated for these two functions when compared to control cells. However, TNF levels were higher in BAL fluid than in plasma. The possible mechanisms involved in the hyperresponsiveness of cells from PCM patients are discussed. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: paracoccidioidomycosis; bronchoalveolar lavage; macrophages; fungicidal activity; blood monocytes